2022
DOI: 10.1111/resp.14400
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of obesity to breathlessness in a large nationally representative sample of Australian adults

Abstract: Background and Objective Breathlessness is prevalent and associated with medical consequences. Obesity is related to breathlessness. However, the magnitude of its contribution has not been clearly documented. This investigation aimed to determine the contribution of obesity to breathlessness by estimating the population attributable fraction (PAF) in a representative sample of Australian adults. Methods A cross‐sectional, nationally representative survey of Australian residents aged ≥18 years was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…In a representative sample of 9769 adults (51% women) in Australia, breathlessness was defined as a self‐reported modified Medical Research Council (mMRC) score ≥2, corresponding to ‘I walk slower than people of the same age on the level because of breathlessness or have to stop for breath when walking at my own pace on the level’, or worse. Extending a previous report using the same database of the prevalence of obesity (28%) and breathlessness (10%), 2 they now estimated an obesity population attributable fraction (PAF) for breathlessness of about 22% (95% confidence intervals, 17%–27%) 8 . This finding means that obesity contributed to an estimated 22% of cases of breathlessness in the study population, when accounting for different sets of potential confounders.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…In a representative sample of 9769 adults (51% women) in Australia, breathlessness was defined as a self‐reported modified Medical Research Council (mMRC) score ≥2, corresponding to ‘I walk slower than people of the same age on the level because of breathlessness or have to stop for breath when walking at my own pace on the level’, or worse. Extending a previous report using the same database of the prevalence of obesity (28%) and breathlessness (10%), 2 they now estimated an obesity population attributable fraction (PAF) for breathlessness of about 22% (95% confidence intervals, 17%–27%) 8 . This finding means that obesity contributed to an estimated 22% of cases of breathlessness in the study population, when accounting for different sets of potential confounders.…”
mentioning
confidence: 62%
“…4,5 Compared with people with normal BMI, breathlessness is more common in people with underweight (BMI <18.5), overweight (BMI 25-30) and especially with obesity (BMI >30)-also after controlling for known confounders such as the presence of other medical conditions. 3,4,6,7 In a recent publication in Respirology, Guo et al 8 take a further step to evaluate the contribution of obesity to breathlessness in the population. In a representative sample of 9769 adults (51% women) in Australia, breathlessness was defined as a self-reported modified Medical Research Council (mMRC) score ≥2, corresponding to 'I walk slower than people of the same age on the level because of breathlessness or have to stop for breath when walking at my own pace on the level', or worse.…”
Section: Obesity Is a Major Contributing Cause Of Breathlessness In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…(10) The Australian national breathlessness survey found that obesity accounted for a quarter of breathlessness symptoms in adults. (12) Deconditioning is a likely important contributing factor that is currently less well quantified. (13) Despite the impact breathlessness has on quality of life (14), sufferers may delay seeking help, normalising their symptoms, (15,16) and frequently experience significant delays in diagnosis and treatment after seeking help.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The Australian National Breathlessness Survey found that obesity accounted for a quarter of breathlessness symptoms in adults. 12 Deconditioning is a likely important contributing factor that is currently less well quantified. 13 …”
Section: Introductionmentioning
confidence: 99%